FERMION THEORY OF COLLECTIVE STATES OF NUCLEI, ITS APPLICATION TO THE STRUCTURE OF REAL SYSTEMS - K.Baktybaev; A. Dalelkhankyzy; M.K.Baktybaev; N.O.Koilyk (Academic Scientific Journal of Computer Science, 2019)
Based on the nucleon-pair shell model, in which the fermionic space is cut by the "realistic" SDoperators by the generalized senority method, the microscopic structure of the collective states of the nuclei of the average atomic weight is studied. In this case, the effects of splitting of single-particle levels on the collective-pair structure of the system are taken into account. To solve such a multiparticle problem, we use the generalized quasispin method and double tensors, which facilitate the calculation of the matrix elements of pair interactions of nucleons. The total Hamiltonian is diagonalized exactly in fermionic space without applying the procedure for mapping fermion operators into bosonic operators. The parameters of the interacting boson model are calculated on the basis of the permuted fermion approach. The theory is applied to the study of the properties of the collective states of even isotopes of ruthenium with N = 58-66. The spectrum of low-energy states is also calculated for the probabilities of E2 transitions in them and they are compared with the available experimental data.